Development and assessment of five-component wall boiling heat flux partitioning model. (January 2023) - Wang, Hongbin; Xiong, Jinbiao; Wang, Ji
Highlights: A five-component wall heat flux partitioning model is proposed for boiling simulation. The model siginifies the modeling of heat transfer mechanisms related to bubble sliding. The model is assessed with the DEBORA experiment data and showed significant improvement for boiling simulation. Abstract: A mechanistic framework of wall boiling model with the total heat flux partitioned into five components, i.e. solid quenching, sliding-induced transient conduction, lift-off induced transient conduction, evaporation and single-phase convection, is developed and implemented into the unsteady two-fluid solver in the OpenFOAM. As important sub-models, bubble departure diameter, lift-off diameter and sliding length are calculated based on force balance analysis. A two-phase wall function is employed to account for the effect of nucleated bubbles on the near-wall turbulence. The developed model framework is assessed with the DEBORA experiment with the R12 as work fluid at the pressure of 1.46 MPa and 2.62MPa. The assessment indicates that the two-phase wall function improves prediction of liquid and vapor velocity profile and that the void fraction, the liquid and wall temperature can be well predicted. Under the condition of lower pressure and higher surface heat flux, bubble grows faster, which increases bubble departure and lift-off diameter. Higher liquid mass flux increases quasi-steady drag force and shear lift force, which consequently reduces the bubble departure and lift-off diameter. Due to large nucleation site spacing, relatively large sliding length appears in the lower-pressure cases. Nucleation awaiting time dominates the bubble departure frequency which increases steeply when the near-wall liquid approaches saturated. Comparing with the RPI model, the current model predicts relatively small evaporation heat flux. The predicted solid quenching and transient conduction heat flux induced by bubble lift-off are less significant in all the cases. The calibrated algebraic bubble size model can be adequate in the simulation of subcooled boiling at high pressure condition.